Looking ahead - vision of the study of geography in Maribor - Konečnik Kotnik, Eva (Journal for Geography, 2013)
This article describes the perspectives of the Department of Geography at the Faculty of Arts Maribor. First, the article focuses on and describes the research perspectives which were pointed out by the present members of the Department of Geography. In the second part, study/pedagogical perspectives of studying geography in Maribor are described from the point of view of the members of the Department. To article concludes with a consideration of the obstacles and the development opportunities for the Department of Geography in Maribor.